Effects of short hypoxic pre-exposure on physiological responses to subsequent hypoxic exercise - Yoshihiko Kubota; Chiho Fukusaki; Shimpei Okaneya; Taketeru Maegawa; Kazuo Narita (Japanese Society of Physical Fitness and Sports Medicine, 2015)
In mountain climbing, short pre-exposure to hypoxia at the midway point of a high mountain is often carried out before heading to a higher altitude. However, the effects of such exposure have not been examined experimentally. This study aimed at investigating the effects of short pre-exposure to hypoxia on physiological responses to subsequent hypoxic exercise. Thirteen male sea-level residents participated in 2 tests. Both tests consisted of 60-min normobaric exposure followed by 15-min stepwise incremental ergocycle exercise (five workloads) under hypoxic conditions (fractional inspired oxygen concentration [FiO2] = 0.167). Conditions during normobaric exposure were hypoxic (FiO2 = 0.167) or normoxic (FiO2 = 0.209). Results of the two-way analysis of variance (oxygen concentration × exercise intensity) showed significant oxygen concentration effects on heart rate (HR), carbon dioxide production (VCO2), and rating of perceived exertion during hypoxic exercise. Significant interaction effects were found in minute ventilation and VCO2. Post hoc tests compared these parameters after hypoxic exposure with those after normoxic exposure at each workload, and only showed a significant difference in HR at workload 2. A significant negative correlation was observed between peak oxygen uptake (VO2) measured in normoxia and ratio of arterial oxygen saturation (SpO2) after hypoxic exposure to that after normoxic exposure at workload 5. The present study could not clearly show through post hoc tests the significant effects of short hypoxic pre-exposure on physiological responses to subsequent hypoxic exercise, while it indicated that those with relatively higher peak VO2 showed a greater decrease in SpO2 during hypoxic exercise after hypoxic exposure than after normoxic exposure.